MENINGKATKAN HASIL BELAJAR MUATAN BAHASA INDONESIA MATERI INFORMASI TENTANG PERUBAHAN BENTUK ENERGI MELALUI METODE PRAKTIK BERPASANGAN PADA SISWA KELAS III SDN 69 KENDARI SEMESTER 2 TAHUN PELAJARAN 2021/2022 - Yohana Pasedan (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
As for the reality that happened in class III at SDN 69 Kendari, based on daily test scores, especially in Indonesian Language learning, there were several students who had met the KKM scores and most of them had not met the KKM scores. so the number of students who have completed is only 9 students out of a total of 29 students, while those who have not completed are 20 students out of a total of 29 students so students who have not completed are greater than students who have completed. From the results of the pre-action tests and initial observations, the researcher who is also a class III teacher decided to use a varied method which made students not bored and made students enthusiastic in learning, in this case the researcher used the practice method in pairs. This study uses an action research model (action research). This research was conducted in class III SDN 69 Kendari. Researchers conducted research here with the consideration that researchers are teachers in this school. The subjects of this study were class III SDN 69 Kendari, with a total of 29 students. This research was carried out at the beginning of the new 2021/2022 school year, namely January - April 2022. Data collection techniques in this study were testing, observation and documentation techniques. In the pre-cycle, the classical student learning outcomes were 31.03% in the "very low" category, in the first cycle the percentage was 68.96% in the high category, while in the second cycle the percentage was classically 100% in the "very high" category. In cycle I, class activity has an average of 2.85 with the criteria of "good", and in cycle II, it also has an average of 3.21 with the criteria of "good". While the percentage of student activity in the first cycle is classically 75% in the "good" category and in the second cycle the percentage is 85% and the category is "very good". In addition to the percentage of students' activeness, what will also be concluded is the learning outcomes of students. The results of the second cycle evaluation showed that classical learning mastery reached (100%) with an average final score of students reaching (85.88), previously in the pre-cycle it was known that classical learning mastery reached (31.03%) with an average final test score students reached (65.62) and in the first cycle classical learning mastery reached (68.96%) with an average final test score of students (75). The pair practice method can be applied to Information Materials About Changes in Energy Forms because it can solve problems so that activity and cooperation increase and can develop students' motivation in learning the material. From this information it can be concluded that the practice method in pairs can be applied to Information Material About Changes in Energy Forms and can improve learning outcomes in class III Semester 2 SDN 69 kendari Academic Year 2021/2022.